Risk factors of cerebrospinal fluid leakage after neuroendoscopic transsphenoidal pituitary adenoma resection: a systematic review and meta-analysis - Zhao, Jiahui; Wang, Shisong; Zhao, Xudong; Cui, Haohao; Zou, Cunyi (Frontiers in Endocrinology, 2024)
Introduction:Cerebrospinal fluid (CSF) leakage is common and might lead to severe postoperative complicationsafter endoscopic transsphenoidal pituitary adenoma resection. However, the risk factors of postoperative CSF leakage are still controversial. This article presents a systematic review toexplore theexplicit risk factors ofCSF leakage after endoscopic transsphenoidal pituitary adenomaresection. Methods:PRISMA and AMSTAR guidelines were followedto assess the methodological quality of the systematic review. PubMed, Medline, Embase, Web of Science, Cochrane, Clinical Trails, CNKI, CBM, WanFang, and VIP databases were searched for all studies on postoperative CSF leak risk factors. The quality of the included studies was assessed by the Newcastle-Ottawa scale. Review Manager 5.4 software was used tocalculate the pooled effect size of potential factors with statistical significance. Results:A total of6775 patients with pituitary adenoma across 18 articles were included, containing 482 cases of postoperative CSF leakage (accounting for 7.11%). All of the articles had a quality score > 5, indicating good quality. Meta-analysis showed that an increased risk of CSF leak was found for higher levels of BMI (MD=1.91, 95% CI (0.86,2.96), bigger tumor size (OR=4.93, 95% CI (1.41,17.26)), greater tumor invasion (OR=3.01, 95% CI (1.71, 5.31), the harder texture of tumor (OR=2.65, 95% CI (1.95,3.62)), intraoperative cerebrospinal fluid leakage (OR=5.61, 95% CI (3.53,8.90)), multiple operations (OR=2.27, 95% CI (1.60,3.23)). Conclusion:BMI, multiple operations, tumor size, tumor invasion, hard texture, and intraoperative cerebrospinal fluid leakage are the risk factors of postoperative CSF leakage. Clinical doctors should payattention tothese risk factors, and conduct strict skull base reconstruction and careful postoperative management.